Effect of Breed on the Volatile Compound Precursors and Odor Profile Attributes of Lamb Meat - Can Zhang; Hao Zhang; Ming Liu; Xin’gang Zhao; Hailing Luo (Foods, 2020)
The objective was to characterize the effect of breed on the volatile compound precursors and odor profile attributes and to provide an insight into improving the lamb production and meat flavor. Three-month-old Tan (n = 10), Hu (n = 10) and Dorper lambs (n = 10) were raised for 90 days in single barns. Longissimus thoracis et lumborum muscle of all lambs were collected for analysis of intramuscular fat, fatty acids, amino acids, and volatile compounds. The results showed Tan and Hu accumulated more intramuscular fat and saturated fatty acid than Dorper. However, Tan had lower linoleic acid, alpha linolenic acid and total polyunsaturated fatty acid proportion than Dorper. Amino acid in Dorper was significantly higher than Tan and Hu. Furthermore, (E)-2-hexenal was only found in Tan lambs, while (E)-2-nonenal and (E,E)-2,4-nonadienal were only found in Dorper lambs. Hu had the fewest volatile compounds. The results of this study demonstrated that Dorper had larger proportion of polyunsaturated fatty acids (PUFA), amino acid and volatile compounds than Tan and Hu. However, the specific PUFA derivates of Dorper had a negative impact on the odor profile. Hence, we suggest that further works should be focused on crossbreed lambs by Dorper and Tan, to enhance the lamb production and improve meat flavor.